The anthropology of religious conversion - Buckser, Andrew, 1964-; Glazier, Stephen D. (Rowman & Littlefield Publishers, 2003)
The Anthropology of Religious Conversion paints a picture of conversion far more complex than its customary image in anthropology and religious studies. Conversion is very seldom simply a sudden moment of insight or inspiration; it is a change both of individual consciousness and of social belonging, of mental attitude and of physical experience, whose unfolding depends both on its cultural setting and on the distinct individuals who undergo it. The book explores religious conversion in a variety of cultural settings and considers how anthropological approaches can help us understand the pheno.